2019
DOI: 10.1080/2314808x.2019.1670425
|View full text |Cite
|
Sign up to set email alerts
|

HPLC-DAD profiling and inhibitory potentials of ethylacetate and aqueous extracts of Talinum triangulare on key enzymes linked to type-2 diabetes (α-amylase and α-glucosidase) and oxidative stress (monoamine oxidase)

Abstract: HPLC-DAD profiling and inhibitory potentials of ethylacetate and aqueous extracts of Talinumtriangulare on key enzymes linked to type-2 diabetes (α-amylase and α-glucosidase) and oxidative stress (monoamine oxidase),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(36 reference statements)
0
2
0
Order By: Relevance
“…The plant is commonly utilized in the preparation of soups and other culinary delicacies [24]. Research studies have revealed that the plant is rich in natural compounds like flavonoids and polyphenols [25,26]. The plant has exhibited a wide range of biological and pharmaceutical properties, including anti-inflammatory, anti-fungal, neuroprotective, and anti-bacterial activities [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The plant is commonly utilized in the preparation of soups and other culinary delicacies [24]. Research studies have revealed that the plant is rich in natural compounds like flavonoids and polyphenols [25,26]. The plant has exhibited a wide range of biological and pharmaceutical properties, including anti-inflammatory, anti-fungal, neuroprotective, and anti-bacterial activities [27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…The plant has exhibited a wide range of biological and pharmaceutical properties, including anti-inflammatory, anti-fungal, neuroprotective, and anti-bacterial activities [27][28][29]. Additionally, in our previous studies, we reported the antioxidant properties [30], and presence of a number of bioactive compounds identified from the aqueous extract of Tt [25]. However, there is a paucity of information on computational interactions of these compounds with AChE and BChE activities in the prevention/management of neurodegeneration diseases such as AD.…”
Section: Introductionmentioning
confidence: 99%